ANALISIS KEPUASAN PASIEN RAWAT INAP KELAS III DI RSUD KOTA KOTAMOBAGU - Mongkau, Fernando M; Ratag, Gustaaf A. E.; Manampiring, Aaltje E. (Coping: Community of Publishing in Nursing, 2021)
Health is one of the human rights, and by the mandate of the 1945 Constitution of the Republic of Indonesia, it has been emphasized that everyone has the right to health services. Fulfillment of patient papacy at Kotamobagu City Hospital to increase service capacity and status of Kotamobagu City Hospital which is in the Important BLUD stage, public satisfaction can be fulfilled by examining 5 dimensions in health services, namely reliability, assurance, tangibility, empathy, and responsiveness. The research objective was to obtain in-depth information about the satisfaction level of class III inpatients at Kotamobagu City Hospital. A qualitative approach with a descriptive approach using in-depth interviews. conducted from October to February 2021, at the Kotamobagu City Hospital, 18 patients in the inpatient room were the study informants, the patient informants were taken as samples using an accidental sampling technique. Data analysis using content analysis techniques. The results showed that the dimensions of reliability were still there were specialist doctors who were not punctual inpatient care, dimensions of responsiveness, lack of courtesy and friendliness of officers to patients, and dimensions of physical evidence of hospital facilities and infrastructure were incomplete. Three things have not been maximized so that it affects patient satisfaction. These three things are to further improve the punctuality of specialists in examining patients, courtesy, and friendliness of officers to patients, and incomplete facilities and infrastructure. Keywords: Patient Satisfaction, Quality of Service, Inpatient